Variability in Postharvest Decay Among Apple Cultivars - Spotts, R A (Plant disease, 1999)
The level of resistance to decay caused by four fungal pathogens, the force required to break the epidermis, and the extent of open sinuses as measures of potential decay resistance were determined for the fruit of several apple cultivars. No single cultivar was the most resistant to each of the four pathogens in this study. In addition, each cultivar that was the most resistant to one pathogen also was the most susceptible to one of the other pathogens. However, Royal Gala was the most resistant to the wound pathogens Botrytis cinerea, Penicillium expansum, and Mucor piriformis. Fuji and Oregon Spur II were more resistant than other cultivars to Pezicula malicorticis. The epidermis (skin) of Fuji and Granny Smith were the most resistant to puncture, requiring an average of 81.5 and 87.0 Newtons, respectively, to break the epidermal layer. Fuji had the highest percentage of fruits with open sinuses, with a mean of 38%, whereas Braeburn had 0% of fruit with open sinuses. The cultivar information presented herein may be a valuable measure of decay resistance and may be of use to the apple industry